Forecasting Mortality for Kazakhstan Using the Lee-Carter Model - KNYKOVA, Akzharkyn; SAPIN, Azat (Journal of Advanced Research in Law and Economics; Vol 8 No 6 (2017): JARLE Volume VIII Issue 6(28) Fall 2017, 2017)
The Lee-Carter Model is one of the most popular methodologies for forecasting mortality rates. The model has been used very successfully in the U.S. and several other countries. The purpose of this paper is to develop general and sex-specific mortality forecasting model using historical mortality data for Kazakhstan from 1999 to 2015, based on the statistical time series techniques attributed to Lee, and Carter (1992). The Singular Value Decomposition (SVD) is used to estimate the model’s parameters and the autoregressive moving average (ARIMA) is used to forecast general and sex-specific mortality rates for the time period from 2016 to 2021. Also forecasted values of life expectancy are obtained for both males and females using forecasts of mortality rates.